Correct-ed through construction: a model-based approach to embedded systems reality - Jackson, Ethan; Sztipanovits, Janos (Engineering of Computer Based Systems, 2006. ECBS 2006. 13th Annual IEEE International Symposium and Workshop on, 2006)
We present a design methodology for specifying embedded systems that addresses the complex nature of embedded systems design. Our approach uses modern model-based techniques to correct specifications as they are constructed, driving the engineer towards a more correct specification. We also present a concrete specification language based on this methodology